Factors that influence consumer viewing behavior in large-scale preview screenings in Chinese film market. - Cong Shen; Xin Hao (PLoS ONE)
The large-scale preview screenings during the summer season of 2023 hit box office records in the Chinese film industry. The rising box office earnings of widely distributed films indicate an increasing consumer propensity to watch movies in the post-pandemic period. Nevertheless, there is a lack of research about the consumption patterns associated with large-scale preview screening activity. This study examines the determinants of large-scale preview screening behavior by building a research model based on the theory of planned behavior. After interviewing 251 consumers from Zhengzhou, a newly selected first-tier city in China, we used Amos to analyze their patterns in attending large-scale preview screenings. According to our empirical study, consumers' intention to watch movies on large-scale preview screening is positively and significantly affected by their perceived behavioral control, social network, and consumption expectation. Perceived behavioral control had the most significant influence, followed by social network and consumption expectation. These elements have a favorable and significant influence on consumers' intention to watch movies. This study examines the main factors that influence consumers' movie-watching habits and identifies the behavioral patterns that affect large-scale preview screening cinema attendance. The findings of this study can be a reference for increasing consumers' passion for watching films. It offers vital recommendations for the recovery and sustainable growth of China's film market in the post-pandemic period.